2022
DOI: 10.3390/jpm12091462
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Turnover Due to Hypothyroidism or Anti-Resorptive Treatment Does Not Affect Whole-Body Glucose Homeostasis in Male Mice

Abstract: Bone is a large and dynamic tissue and its maintenance requires high amounts of energy as old or damaged bone structures need to be replaced during the process of bone remodeling. Glucose homeostasis is an essential prerequisite for a healthy bone and vice versa, the skeleton can act as an endocrine organ on energy metabolism. We recently showed that hypothyroidism in mice leads to an almost complete arrest of bone remodeling. Here, we aimed to investigate whether the profound suppression of bone remodeling af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A previous study confirmed that T 3 stimulates glucose uptake via glucose transporters GLUT1 and GLUT3 into osteoblasts in vitro, however, GLUT4 was not investigated in that study 55 . Vice versa, we have previously shown that hypothyroidism leads to reduced glucose uptake and correspondingly low Slc2a4 expression in bone tissue in mice 56 . Linking glucose metabolism to BMP signaling, BMPR1A was reported to regulate the expression of glucose transporter Slc2a1 in chondrocytes in vivo 57 and its BMP ligand BMP2 was shown to upregulate Slc2a4 expression in adipocytes 58 .…”
Section: Discussionmentioning
confidence: 92%
“…A previous study confirmed that T 3 stimulates glucose uptake via glucose transporters GLUT1 and GLUT3 into osteoblasts in vitro, however, GLUT4 was not investigated in that study 55 . Vice versa, we have previously shown that hypothyroidism leads to reduced glucose uptake and correspondingly low Slc2a4 expression in bone tissue in mice 56 . Linking glucose metabolism to BMP signaling, BMPR1A was reported to regulate the expression of glucose transporter Slc2a1 in chondrocytes in vivo 57 and its BMP ligand BMP2 was shown to upregulate Slc2a4 expression in adipocytes 58 .…”
Section: Discussionmentioning
confidence: 92%